Naturally gluten-free flours are commonly contaminated, while commercially produced gluten-free flours are relatively safe: a market-based study in Turkey - Öcal, Hacer Yalçimin; Özel, Hülya Gökmen (Frontiers in Nutrition, 2025)
BackgroundGluten contamination and unintentional gluten exposure are serious health concerns for patients with celiac disease. Gluten-free (GF) products may become contaminated at any stage, including harvesting, production, storage, or sale. This study, conducted in Turkey, aimed to compare gluten contamination levels in commercially produced gluten-free (CGF) and naturally gluten-free (NGF) flours—both packaged and unpackaged—across different grain types, and to evaluate the influence of point-of-sale and storage conditions on contamination levels.MethodsA total of 163 flour products, including oat, buckwheat, corn, and rice flours (n = 54 CGF, n = 56 unlabeled/packaged NGF, and n = 53 unlabeled/unpackaged NGF), were analyzed for gluten content using the EU-approved R5 ELISA method.ResultsGluten contamination was detected in 16.67% of CGF flours, 50% of unlabeled/packaged natural GF flours, and 84.91% of unlabeled/unpackaged natural GF flours. CGF flours were significantly less contaminated than NGF flours (p < 0.001). However, 16.67% of CGF flours exceed the 20 mg/kg threshold, indicating that gluten-free labeling alone does not always guarantee safety. Oat and buckwheat flours had significantly higher contamination levels than corn and rice flours (p < 0.001). Although GF flours stored in dedicated sections had lower gluten levels, the difference was not statistically significant. A negative relationship was observed between proximity to gluten-containing products and gluten levels in unpackaged NGF flours (p < 0.001). Additionally, gluten contamination increased significantly in unlabeled/unpackaged flours when shared spoons were used (p = 0.001).ConclusionGluten contamination is common in NGF products, whereas CGF products are relatively safe. These findings highlight the importance of controlled production and storage practices as well as strengthened verification and certification procedures for gluten-free labeling to minimize the risk of gluten contamination.